2002
DOI: 10.1080/003655102321004576
|View full text |Cite
|
Sign up to set email alerts
|

Serum and plasma as alternative sample types in analysis of cardiac markers in the clinical routine

Abstract: There is an increasing demand for the results of cardiac markers (troponin I or T, creatine kinase MB mass and myoglobin) to be made available promptly after sample-taking. In order to shorten the turnaround time, the possibility of using EDTA- or heparin-plasma instead of serum was investigated. The study population comprised 391 patients with acute chest pain. Four different instruments and systems routinely used in Finland giving quantitative results were studied for the assays of creatine kinase isoenzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…CK activity of the serum and plasma samples was measured photometrically using the IFCC method [7,8] Table I. The methods used by the laboratories participating in the surveys during the study period are presented in Table II.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…CK activity of the serum and plasma samples was measured photometrically using the IFCC method [7,8] Table I. The methods used by the laboratories participating in the surveys during the study period are presented in Table II.…”
Section: Measurementsmentioning
confidence: 99%
“…The ElecsysH 2010 electrochemiluminescent system (Roche Diagnostics, Mannheim, Germany) was used for measuring CK-MBmass (CK-MB STAT) and cTnT (Troponin T STAT) [8]. For cTnI, two assays, the AxSYMH microparticle enzyme immunoassay for cTnI (AxSYMH Troponin-I, Abbott Diagnostics Inc., Abbott Park, Ill., USA) [9] and the ImmuliteH 2000 two-site chemiluminescent immunoassay for cTnI (ImmuliteH 2000 Troponin I, Diagnostic Products Co., Los Angeles, Calif., USA), which were both available in our laboratory, were used in accordance with the instructions of the manufacturers.…”
Section: Measurementsmentioning
confidence: 99%
“…Accordingly, it was suggested to Brought to you by | University of Georgia Libraries Authenticated Download Date | 6/12/15 3:00 AM adhere to the NACB recommendations to use plasma as the preferred sample for stat analysis, and to calibrate with plasma-based calibrators when this type of sample is used. However, a single EDTA-or heparin-plasma proved suitable for three of the four analyzers, thereby permitting significant shortening of the turnaround time (13). In a further study (12), comparing plasma/serum pairs and studying of the effect of heparin addition to serum, it was concluded that the mean plasma/serum ratio was close to 1, but the plasma/serum variability was large, in one out of a hundred samples leading to an underestimation in plasma up to 46%.…”
Section: Introductionmentioning
confidence: 99%
“…Kardiyak belirteçlerin (troponin I veya T, CK-MB ve miyoglobin) numune alımından hemen sonra erken zamanda sonuç alınmasına yönelik klinesyenler tarafından artan bir talep vardır. Geri dönüş süresini (TAT) kısaltmak için serum yerine EDTA-veya heparinplazma kullanılmaktadır (11). AMI tanısında, daha erken sonuç almak için birçok laboratuvar serum yerine plazmayı tercih etmektedir (12).…”
unclassified